Prediction of compressive strength of nano silica and micro silica from rice husk ash using multivariate regression models - Raji, Mustapha A.; Falola, Boluwatife M.; Enikuomehin, Jesse T.; Oyelade, Akintoye O.; Abiodun, Yetunde O.; Olaniyi, Yusuf A.; Olagunju, Olusola G.; Anyaegbuna, Kosisochukwu L.; Abdulkareem, Musa O.; Fapohunda, Christopher A. (AI in Civil Engineering, 2024)
The use of agricultural by-products, such as Rice Husk Ash (RHA), in concrete production has gained significant attention as a sustainable alternative to traditional construction materials. This study aims to evaluate and compare the effects of Nano-Rice Husk Ash (NRHA) and Micro-Rice Husk Ash (MRHA) on the compressive strength of concrete. Concrete samples were prepared with varying replacement levels of NRHA (0% to 3%) and MRHA (0% to 14%) and underwent thorough examination through both slump and compressive strength tests conducted at 7, 21, 28, and 56 days. The results showed that NRHA achieved maximum compressive strength at a 1% replacement level, while MRHA reached its peak at a 0.5% replacement level. However, a comparison of the compressive strength of NRHA at 1% (22 N/mm 2 ) against MRHA at 0.5% (21.5 N/mm 2 ) revealed that the marginal difference in strength made MRHA a more cost-effective option due to the lower expenses involved in its preparation. Thus, MRHA presents a more economical solution for achieving comparable compressive strength. Furthermore, the study applied linear, non-linear, and mixed regression analyses to model the properties of NRHA and MRHA concrete based on a comprehensive set of variables. The analysis found that the blended ordinary and logarithmic models provided the best fit, offering superior accuracy compared to linear and non-linear models.